Distribution and storage of soil organic and inorganic carbon under different ecological zones in Xinjiang, China - Yan, An; Li, Baoguo; Huang, Feng; Zhang, Wentai; Jiang, Pingan; Sheng, Jiandong (International Journal of Agricultural and Biological Engineering, 2019)
The objective of this study was to quantify both soil organic carbon (SOC) and soil inorganic carbon (SIC) stocks in different ecological zones in Xinjiang Region, the largest arid and semi-arid region in northwest China. The specific focus was on the vertical distributions of 641 typical soil profiles (0-100 cm). The study region covered five ecological zones: I–Altai/west Junggar; II–Junggar basin; III–Tianshan mountain; IV–Tarim basin; and V–Kunlun-Altun mountains. The zones are categorized by their specific geographical locations from north to south with terrains derived from mountains to basins. The data used in the study were obtained from the first (1960s) and the second (1980s) National Soil Surveys and partially from the field survey of this study conducted in 2013. The results suggest that there are 11.74 Pg SOC and 26.71 Pg SIC total stocks in the 0-100 cm surface soil over the entire study region. The distributions of SOC and SIC were found to be non-uniform. The Tianshan mountain zone has the highest SOC stock, followed by the Tarim basin, Kunlun-Altun mountains, Altai and west Junggar (Altai/west Junggar), and Junggar basin zones. In contrast, the Tarim basin zone had the highest SIC stock, followed by the Tianshan mountain, Kunlun-Altun mountains, Junggar basin, and Altai/west Junggar zones. The SOC content decreases gradually from northwest to southeast and from mountains to deserts; while the SIC content decreases gradually from south to north. The SOC and SIC contents also change with soil depth. Within a given ecological zone, the SOC content increased with increasing soil depth, peaked at about 20-40 cm, then it decreased with the bigger depths below 40 cm. The SIC contents increased gradually from 0 to 40 cm, and then decreased gradually with increasing soil depth over the 40-100 cm depth in all ecological zones except for the Tianshan mountain area. Keywords: ecological zones, soil organic carbon, soil inorganic carbon, carbon storage, vertical distribution DOI: 10.25165/j.ijabe.20191201.3872 Citation: Yan A, Li B G, Huang F, Zhang W T, Jiang P A, Sheng J D. Distribution and storage of soil organic and inorganic carbon under different ecological zones in Xinjiang, China. Int J Agric & Biol Eng, 2019; 12(1): 116–125.